Study of Clinical and Epidemiological Factors in Patients Diagnosed with Rheumatoid Arthritis - Rolando Rodríguez Puga; Yasnier Dueñas Rodríguez (Revista Finlay)
Foundation: rheumatoid arthritis is a chronic autoimmune disease that produces chronic and irreversible joint damage that leads to deterioration in quality of life and permanent disability with a worldwide prevalence of between 1.0 and 1.5 %. Objective: to identify the main clinical-epidemiological characteristics of patients with rheumatoid arthritis in the Eastern Area Teaching Polyclinic of Camagüey. Methods: a descriptive case series study was carried out at the Eastern Area Teaching Polyclinic of Camagüey. From the universe of 108 patients, a sample of 102 was selected, once the selection criteria were applied. The variables were studied: age group, sex, skin color, years of diagnosis, clinical signs and symptoms, risk factors; as well as complications presented. SPSS was used to process the data and they were expressed in absolute values and percentages. Results: the age group of 60 years and older predominated (45.0 %), women (75.5 %), patients of white skin color (66.7 %), with rheumatoid arthritis of 16-20 years of evolution (22.5 %), vasculitis (25.5 %) and pain (94.1 %) among the main signs and symptoms, while coffee consumption (69.6 %) and female sex were found among the risk factors. modifiable and non-modifiable risk. Osteoporosis was the most notable of the complications presented (69.6 %). Conclusions: in the series studied, female sex, advanced age, pain as the main symptom, as well as osteoporosis stood out among the complications presented.